Holocene earthquakes on the Tambomachay fault near Cusco, Central Andes - Rosell Guevara, Lorena Nicole (2023)
A system of active normal faults around the city of Cusco have severely damaged the city in major earthquakes in pre-hispanic times, 1650 and 1950 CE. Detailed studies of these faults adjacent to Cusco are therefore needed to build an understanding of seismic hazard in the region. We present new geomorphological and paleoseismological evidence for multiple Holocene earthquakes on the Tambomachay Fault, a 20 km-long normal fault that runs along the northern margin of the Cusco Basin. The western segment of the fault preserves fault scarps that cut moraine crests with a mean throw of 4.3 ± 0.4 m. We determine a 13.8 ± 0.6 ka depositional age of these moraines using 10Be cosmogenic surface-exposure dating of boulders embedded in the moraines, implying a Holocene-average fault slip rate of 0.3 ± 0.1 mm/yr. We also excavated a trench across the moraine crests. By reconstructing the trench stratigraphy with radiocarbon dating, we identified three surface-rupturing earthquakes over the last 8–9 ka. The oldest earthquake occurred between 8.5 and 8.3 ka, a second event between 6.8 and 5.5 kyrs, and the most recent earthquake between 1.2 and 0.9 ka. All of the ruptures predate Inca times (>1 ka). These surface-rupturing earthquakes are likely to have had moment magnitudes of Mw 6.4-6.9. Similar events have the capacity to severely damage modern-day Cusco due to their proximity to the city, which now has a population of 500,000.